(3GdSeSQI hGdhSGWI GdJLGQjI aj VhA GdbGfhf hGdGLJgGO GdbVGFj (B/s - (3GdCMeO, MSGes ((3HjQhJ (B:s (3efThQGJ GdMdHj GdMbhbjI,s, 2012)
(3jJfGhd GdcJGH HTQM (B"(3GdSeSQI hGdhSGWI GdJLGQjI aj VhA GdbGfhf hGdGLJgGO GdbVGFj(B" (3MjK Cf GdSeSQI XGgQI bOjeI GbJVJgG EMJjGLGJ GdqJLGQI dJSgjd GdqJYGed Hjf GdJLGQ heY EROgGQ GdJLGQI GdHMQjI hGdHQjI hXghQ GdeQGaF hGdCShGb GdJLGQjI GROgQJ gPg GdegfI hJTYqHJ HCTcGdgG aj LejY GdfhGM GdJLGQjI, hbdeG NdG bGfhf JLGQj eYGUQ Gdjhe ef PcQ GdSeSQI hCfhGYgG hTQhWgG hCUhdgG hNdGaGJgG(B.s
(3HHdjhLQGajI (B: (3UaMI (B243-245.s
Keywords: (3GdbGfhf GdJLGQjs -- (3dHfGfs; (3GdHhQUGJs -- (3bhGfjf hJTQjYGJs -- (3dHfGfs; (3GdSeSQIs -- (3bhGfjf hJTQjYGJs -- (3dHfGfs